Concentrations of Mineral in Amniotic Fluid and Their Relations to Selected Maternal and Fetal Parameters - Suliburska, J. (Biol Trace Elem Res, 2015)
The concentrations of various trace elements in amniotic fluid (AF) change over the course of pregnancy, with gestational age and fetus growth. The aim of the present study was to evaluate the concentrations of selected essential and toxic elements in AF and their relations to maternal and fetal parameters. The study was carried out in 39 pregnant women, aged 34.6 ± 4.7 years, between weeks 16 and 26 of gestation. Amniotic fluid samples were obtained during the standard procedure of amniocentesis in high-risk patients for chromosomal abnormalities. An inductively coupled plasma mass spectrometry (ICP-MS) technique was used to determine the levels of Al, As, Ba, Cd, Co, Cr, Cu, Mg, Mn, Ni, Sr, U, and V in AF. Body mass and blood pressure were measured in all the women. The basic parameters of fetal development were also assayed. It was found that the age of the mother, the gender of the fetus, and the week of the pregnancy may affect the concentrations of mineral in the amniotic fluid. Moreover, several significant correlations between the essential and toxic elements and maternal and fetal parameters were observed. In particular, negative and positive correlations between fetal parameters and magnesium and copper levels in AF, respectively, were seen. The present findings demonstrate the association between minerals in AF and fetal development.